Serotoninergic antidepressants combination in psilocybin-assisted psychotherapy: a case report - Do, André; Michaud, Vanessa; Stephan, Jean-François; Moreau, Miltiadis; Benoît, Élise; Bérubé, Félix-Antoine; Bibaud-De Serres, Antoine; Taillefer, Alain; Vincent, Philippe (Frontiers in Psychiatry, 2024)
Psilocybin has reemerged as a promising treatment for difficult-to-treat depression (DTD). Although there is limited evidence regarding interactions between psilocybin and other psychotropic drugs, clinical trials require that patients discontinue their antidepressants before study entry to isolate the benefits of psilocybin and to minimize the risk of adverse events. We present the first case of an adult patient with DTD who received psilocybin-assisted psychotherapy (PAP) in combination with two serotoninergic antidepressants (duloxetine and vortioxetine). Since he displayed a partial response after the first PAP session, he agreed to discontinue duloxetine (but refused to stop vortioxetine) before the second PAP session to see if it could improve the therapeutic efficacy of psilocybin. However, his anxiety and depressive symptoms worsened. Psilocybin was well-tolerated in both PAP sessions; mild headaches were the main adverse effects experienced by the patient, and there were no cardiovascular safety concerns. This case report suggests that serotoninergic antidepressants combination with psilocybin appears to be safe and that antidepressant discontinuation prior to PAP may not be necessary. Since the continuation of antidepressants during PAP has the potential to improve treatment acceptability and accessibility, future research should assess whether psilocybin can be administered concurrently with antidepressants.